2017
DOI: 10.1126/science.aao5676
|View full text |Cite
|
Sign up to set email alerts
|

Vasohibins encode tubulin detyrosinating activity

Abstract: Tubulin is subjected to a number of posttranslational modifications to generate heterogeneous microtubules. The modifications include removal and ligation of the C-terminal tyrosine of ⍺-tubulin. The enzymes responsible for detyrosination, an activity first observed 40 years ago, have remained elusive. We applied a genetic screen in haploid human cells to find regulators of tubulin detyrosination. We identified SVBP, a peptide that regulates the abundance of vasohibins (VASH1 and VASH2). Vasohibins, but not SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
223
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(239 citation statements)
references
References 33 publications
(23 reference statements)
12
223
2
2
Order By: Relevance
“…Microtubules receive a variety of post‐translational modifications including tubulin detyrosination. VASH2 has recently been shown to have TCP activity . In accordance with this evidence, the present study showed that VASH2 stimulated metastatic activity of PDAC cells, at least in part, through its TCP activity within the cell.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Microtubules receive a variety of post‐translational modifications including tubulin detyrosination. VASH2 has recently been shown to have TCP activity . In accordance with this evidence, the present study showed that VASH2 stimulated metastatic activity of PDAC cells, at least in part, through its TCP activity within the cell.…”
Section: Discussionsupporting
confidence: 91%
“…Vasohibins have recently been identified to have TCP activity, which deletes a tyrosine residue from the carboxy‐terminus of α‐tubulin . We confirmed that detyrosinated tubulin was decreased in Vash2‐knockdown KPC cells and tissue of orthotopic tumors (Figure A‐C).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Shortly after, it was found that a cytosolic tubulin carboxypeptidase (TCP) activity, preferentially working on polymerized tubulin, was responsible for the cleavage of the C-terminal tyrosine (Gundersen, Khawaja, & Bulinski, 1987; Hallak, Rodriguez, Barra, & Caputto, 1977). However, the identity of TPC(s) mediating this cleavage remained elusive for more than three decades and only recently were identified by two different groups (Aillaud et al, 2017; Nieuwenhuis et al, 2017). Vasohibin-1 and its homologue Vasohibin-2, previously described has angiogenic factors, were shown to catalyse detyrosination when in complex with a chaperone-like peptide - small vasohibin binding protein (SVBP).…”
Section: Introductionmentioning
confidence: 99%